SQL essentials - Blum, Richard 1962-; Taylor, Allen G. (John Wiley & Sons, Inc., 2025)
SQL Essentials For Dummies is your quick reference to all the core concepts of SQL-a valuable common standard language used in relational databases. This useful guide is straightforward-with no excess review, wordy explanations, or fluff-so you get what you need, fast. Great for a brush-up on the basics or as an everyday desk reference, this book is one you can rely on. Perfect for supplementing classroom learning, reviewing for a certification, and staying knowledgeable on the job, SQL Essentials For Dummies is the convenient, direct, and digestible reference you've been looking for.
Includes index
Keywords: SQL (Computer program language); Relational databases; SQL (Langage de programmation); Bases de données relationnelles